Clinical applications of the Groningen Defecation and Fecal continence questionnaire in constipation, fecal incontinence, and irritable bowel syndrome - Ding Haibo; Sun Ge; Gao Xianhua; Zhang Wei (结直肠肛门外科)
This article introduces the background, content, and validation of the Groningen Defecation and Fecal continence questionnaire and compares it with commonly used assessment scales for constipation, fecal incontinence, and irritable bowel syndrome. The epidemiology, etiology, and application efficacy of the Chinese version of the Groningen Defecation and Fecal continence questionnaire in the Chinese population are analyzed, and the future application prospects of the questionnaire are summarized. This provides a reference for Chinese researchers in selecting appropriate scales for the diagnosis, treatment, and research of functional gastrointestinal disorders.